COMMISSIVE SPEECH ACT IN ADVERTISEMENT OF THE MAGAZINE NOW! JAKARTA - Florensya Natalia; Yusniaty Galingging (Prodi Sastra Inggris UKI, 2019)
This writing is focused on the commissive speech act in the magazine NOW! Jakarta. The commissive speech act is one of many illocutionary speech acts which essentially involve the speaker committing himself to behave in some required ways, for instance promising and swearing. This study aims to find out and analyze the categories of commissive Speech Act of English Advertisements in Magazine Now! Jakarta. NOW! Jakarta Magazine, editions February and March 2016 will be the data used in this study. The writer analyzes the collected data descriptively by using the theory of Austin. The result shows that there are forms of illocutionary speech acts in every text of an advertisement; it is used to give information and emotional response. There is the commissive function of offering in every utterance and the other commissive function such as persuading, guaranteeing, undertaking, and promising which are found in advertisements of consumers. It is expected that this study may help the students or readers to comprehend the illocutionary act, particularly about the commissive speech act in the advertisement of consumers in the magazine NOW! Jakarta.